Dimensions of Linguistic Space: Variation - Multilingualism Conceptualisations Dimensionen des sprachlichen Raums: Variation - Mehrsprachigkeit - Konzeptualisierung - Bülow, Lars; Herbert, Kristina; Fischer, Ann Kathrin (Schriften zur deutschen Sprache in Oesterreich, 2019)
This volume focuses on the use and structure of the German language in Austria. In addition, the aim of the book is to compare the linguistic conditions in Austria with those in other German speaking countries. The 20 articles present current findings from the research fields of variation, contact and perception. Der Band widmet sich schwerpunktmäßig der Verwendung und Struktur der deutschen Sprache in Österreich. Ziel des Sammelbandes ist es außerdem, die sprachlichen Verhältnisse in Österreich mit denjenigen in anderen deutschsprachigen Ländern zu vergleichen. In 20 Beiträgen werden daher aktuelle Forschungsergebnisse aus den Forschungsbereichen Variation, Kontakt und Perzeption vorgestellt.